Effect of eugenol on the useful life of sauce from chile jalapeño (Capsicum annum) and papaya (Carica papaya) (Nexo Revista Científica, 2020)
This work aimed to measure the effect of eugenol on the shelf life of a hot sauce from jalapeño pepper (Capsicum annuum) and papaya (Carica papaya). Cloves were tested as test material, using different forms of eugenol extraction as essential oil. Its use as a preservative in a sauce was evaluated by means of accelerated methods for 30 days at a temperature of 280 C ± 20 C and was compared with sodium benzoate (control) according to the Codex Alimentarius regulations (250 mg / kg). The results determined that eugenol had an inhibitory effect on the change in hot sauce, prolonged its shelf life, indicating its potential application in the food industry, making it a natural preservation alternative, the use of which will help to decrease the toxicological risks provided by synthetic preservatives.